Application of the PjBL-STEM Model to Improve Science Literacy of Class XI SMAN Plus Student - Annisa Al Fatihah; Y Yennita (Science Education Department of Mathematics and Natural Sciences Education Faculty of Teacher Training and Education, Universitas Riau in collaboration with the Association of Indonesian Science Educators (PPII), 2023)
This research aims to improve students' scientific literacy skills by using the Project-based learning (PjBL) learning model integrated with the STEM (science, technology, engineering, and mathematics) approach in class XI MS 3 students at SMAN Plus, Riau Province. The research used the Classroom Action Research (PTK) method with a total of 29 students, which was carried out in two cycles, with each PTK cycle consisting of five steps, namely: 1) localizing the problem, 2) planning, 3) action and observation, 4) analyzing data, and 5) reflection. The scientific literacy studied includes 3 competencies, namely explaining phenomena, interpreting, evaluating, and designing scientific investigations. The results of the analysis of students' scientific literacy abilities from the comparison of cycle I and cycle II showed an increase in scientific literacy scores, namely from 64.3 to 72.1. Based on the research results, it can be concluded that the application of the PjBL-STEM learning model is effective in improving students' scientific literacy skills in learning Physics, especially in class XI MS 3 SMA Plus Pekanbaru.